2000
DOI: 10.1055/s-2000-10005
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Presence of Helicobacter Pylori Genome in the Saliva of Patients With Hyperemesis Gravidarum

Abstract: Recently, possible involvement of Helicobacter pylori (H. pylori) in hyperemesis gravidarum have been reported based on serological studies and the therapeutic effects of antibiotics. In this study, we examined for the presence of H. pylori genome [by (PCR) of saliva] in combination with serological techniques. Thirty-four patients with hyperemesis and 29 normal pregnant subjects were examined for serum anti-H. pylori IgG antibodies and PCR of saliva. By serum antibody test, 16 of 34 hyperemesis patients (47.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…In a metaanalysis of 14 case-control studies, which included a total of 1732 patients and controls, an association between the presence of helicobacter pylori and HG was suggested, although not all of the analysed studies reached statistical significance [odds ratio from 0.55 to 109.33, confidence interval (CI) 95%] [6]. Nevertheless, in one study examining both saliva (61.8% detection of helicobacter pylori in patients with HG versus 27.6% in symptom-free pregnant women) and serum (52.9% versus 20.7%) for the bacterium results were significant ( P < 0.0001, CI 95%) [17], as were cytotoxin-associated gene A and serum findings in a Chinese study [19]. Two observational studies of five patients with HG reported no improvement in symptoms in response to standard drug treatment.…”
Section: Aetiologymentioning
confidence: 99%
“…In a metaanalysis of 14 case-control studies, which included a total of 1732 patients and controls, an association between the presence of helicobacter pylori and HG was suggested, although not all of the analysed studies reached statistical significance [odds ratio from 0.55 to 109.33, confidence interval (CI) 95%] [6]. Nevertheless, in one study examining both saliva (61.8% detection of helicobacter pylori in patients with HG versus 27.6% in symptom-free pregnant women) and serum (52.9% versus 20.7%) for the bacterium results were significant ( P < 0.0001, CI 95%) [17], as were cytotoxin-associated gene A and serum findings in a Chinese study [19]. Two observational studies of five patients with HG reported no improvement in symptoms in response to standard drug treatment.…”
Section: Aetiologymentioning
confidence: 99%
“…9 A recent promising focus is on suppression of HG by successful eradication of Helicobacter pylori. 10,11 A recent review by Philip 12 discusses other suggested causes of HG.…”
mentioning
confidence: 99%
“…Effect estimates of the association between H. pylori and HG from previous case-control studies on different populations in different geographic areas, varies a lot in magnitude showing very strong positive associations to none. In 1998, Frigo et al [8] first linked HG to H. pylori reporting a significant difference in H. pylori in patients with HG versus pregnant women without HG, and so did other authors the following years [9][10][11][12][13][14][15][16]18]. In 2003, Jacobson et al [22] first reported no association between H. pylori and HG, followed by others [17,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The last decade, H. pylori has been a candidate etiologic factor for HG [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Many of the previous studies have been limited to relatively small sample size reporting only crude effect estimates.…”
Section: Introductionmentioning
confidence: 99%